Large-scale HIV testing in the older population in China: findings from a cross-sectional study. (August 2014) - Xie, Tiansheng; Wang, Guohua; Yan, Haibo; Yang, Liqun; Yu, Wei; Fan, Jun; Ruan, Bing; Wu, Nanping
Summary: Aiming to explore universal HIV testing, and to understand the exact HIV prevalence in the older general population, we conducted a community-based cross-sectional epidemiological investigation in two counties of Zhejiang province, China. Using census strategy and convenience sampling method, those participants who were older than 50 years and met eligibility criteria were enrolled, and HIV prevalence was presented as a crude infection rate. A total of 215, 441 (64.82%) were enrolled into this study, HIV testing was added into their health exam plan and 18 were confirmed as HIV positive, giving a crude rate of 0.84/10, 000. HIV prevalence was higher among men than among women in all age groups ( p < 0.05). Unlike previous research, 14 cases (78%) still had a relatively high CD4 + count; 17 cases (94%) had been infected by sexual transmission. Active large-scale HIV screening by integrating into routine health care can be an effective strategy to find people living with HIV at relative early stage of disease.